Kuznets at 70: The enduring significance of a curve and a hypothesis - James K. Galbraith; Ravi Kanbur; Kunal Sen; Andrew Sumner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Seven decades ago, Simon Kuznets put forward the hypothesis that as economies developed, national inequality would first increase and then decrease-an inverted U-shape. He provided preliminary evidence for the hypothesis on the basis of the limited data available at the time, and theorized the genesis of the curve as arising from the twin forces of structural transformation of the economy and political economy pressures. Seven decades on, the Kuznets curve still has a hold on the development discourse as new data is used to test the hypothesis, new theories are elaborated to explain the evolution of inequality, and the metaphor of an inverse U-shape is extended beyond its original realm of national inequality. With this rich history and background, the time is right to examine the Kuznets curve literature broadly construed. This overview takes stock of what has been learned and highlights emerging research and policy questions.
Keywords: D31; O15; O40; 330; Kuznets; inequality; inverted U; structural transformation; political economy